2005
DOI: 10.1002/jez.a.142
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in DNA synthesis of prothoracic gland cells during larval development and their correlation with ecdysteroidogenic activity in the silkworm, Bombyx mori

Abstract: DNA synthesis in prothoracic gland cells of the silkworm, Bombyx mori, was studied immunocytochemically after in vivo labeling with 5-bromo-2'-deoxyuridine (BrdU), and its developmental changes during the 3rd, 4th, and last larval instars were examined. During the early stages of both the 3rd and 4th larval instars, a dramatic increase in the number of DNA-synthesizing cells of the prothoracic glands was detected. However, during the latter stages of each instar, the number of DNA-synthesizing cells greatly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 39 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…Our previous results indicated that it is not changes in the growth-promoting activity of hemolymph, but changes in the responsiveness of the prothoracic gland cells to the growth factors which may, at least in part, contribute to alterations in DNA synthesis during both the fourth and last larval instars (Gu and Chow, 2005). The exact nature of the growth factor that activates prothoracic gland cell DNA synthesis remains to be explored, but the nutrition-dependent response to the growth factor in prothoracic gland cells is similar to endoreplicating cells in Drosophila (Britton et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Our previous results indicated that it is not changes in the growth-promoting activity of hemolymph, but changes in the responsiveness of the prothoracic gland cells to the growth factors which may, at least in part, contribute to alterations in DNA synthesis during both the fourth and last larval instars (Gu and Chow, 2005). The exact nature of the growth factor that activates prothoracic gland cell DNA synthesis remains to be explored, but the nutrition-dependent response to the growth factor in prothoracic gland cells is similar to endoreplicating cells in Drosophila (Britton et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…because our previous study showed that hemolymph from this stage showed the highest growthpromoting effects (Gu and Chow, 2005). As shown in Figure. 4A, when prothoracic glands from control day 4 and day 5 last instar larvae were incubated in medium containing 10% hemolymph, higher levels of DNA synthesis were observed compared with those in control medium.…”
Section: Possible Mechanism Of the Inhibitory Effect Of Starvationmentioning
confidence: 93%
See 3 more Smart Citations